Analytical Modeling of Dual Winding Surface-mounted Permanent Magnet Synchronous Machine for Hybrid Electric Vehicle Accessory Drive Systems - Tezcan, Murat; Mese, Erkan; Ustoglu, Ilker; Ayaz, Murat (TAYLOR & FRANCIS INC, 2017)
Fast and accurate electromagnetic torque calculation of unconventional Permanent Magnet Synchronous Machines (PMSMs) is very important in order to reduce design effort. Dual winding PMSMs (DWPMSMs) can be categorized as unconventional and commonly available fast design software that usually lacks predicting machine performance. In this study, an analytical modeling approach has been proposed to calculate electromagnetic torque of DWPMSMs, which has motor and generator windings in a single stator core. Conformal mapping is used for the calculation of flux levels at various locations in the machine. Radial and tangential components of flux densities due to magnet and winding are determined analytically. Instantaneous value of electromagnetic torque due to generator or motor windings is calculated by integrating the Maxwell stress tensor in the middle of the air gap. Accuracy of the proposed analytical solution is confirmed with finite element analysis results. For further validation, an experimental setup with a 24-slot 22-pole DWPMSM is used. Experimental results have close agreement with analytical results obtained by conformal transform-based modeling.
Keywords: permanent magnet machine; hybrid electric vehicle (HEV); electric accessory drive system (EADS); dual winding permanent magnet synchronous machine (DWPMSM); analytical modeling; conformal mapping; Maxwell stress tensor; electromagnetic torque calculation; magnetic decoupling; simultaneous motor-generator operation; DC STATOR CONNECTIONS; SLOTTED AIR-GAP; FIELD DISTRIBUTION; COGGING TORQUE; MOTORS; DENSITY; LOAD; AC; Engineering